(untitled) (Fiep Bulletin - online, 2014)
This research has the goal to discuss the matter of gender in the professional field of Physical Education, specifically on the profession of swimming coach. We’ve tried to elucidate the barriers that the high level technical professional of swimming teams usually faces when trying to get in, ascend and remain in this career (Souza de Oliveira, 2002). This essay will be written based on the theoretical- methodological reference of the social representation according to Moscovici (2003). The research presents the professional journey of three swimming coaches (Juçara Trancoso, Letícia Macedo e Rosane Carneiro), former athlets and teachers of Physical Education. We found on the collaborators’ speeches, even though hidden, a discrimination towards the matter of gender in the professional day-by-day referring to the category level of the teams that are trained by women and the constant doubting evaluation on the quality of their work and their ability to command sports teams. The lack of representation of the active coaches helps to increase the gender connection between sports and men.